Transparent reinforced glass ceramics with high stress depth, their manufacturing method and application

By introducing zirconium and zirconium oxygen crystals into transparent heating glass ceramics, and forming high-pressure and high-tension stress layers through multi-stage ion exchange treatment, the problem of poor toughness and drop resistance when the thickness of existing transparent ceramics is less than 1 mm, and a combination of high mechanical properties and excellent optical properties is achieved.

JP7654824B2Active Publication Date: 2025-04-01CHONGQING AUREAVIA HI TECH GLASS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023559767
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-30
Filing Date
2022-12-15
Publication Date
2025-04-01
Estimated Expiration
2042-12-15

AI Technical Summary

Technical Problem

The existing transparent zirconium ceramics have poor toughness and drop resistance when the thickness is less than 1 mm, and clouds and devitriification are prone to occur when the Li and Na ions are added for chemical reinforcement, which affects the optical performance.

Method used

A transparent heated glass ceramic containing zirconium and zirconium oxygen crystal is used, with a compressive stress layer on the surface, a thickness of at least 14%, and is formed by a multi-stage ion exchange treatment to form a high compressive stress and high tensile stress layer, ensuring the high mechanical properties and excellent optical properties of the ceramic.

Benefits of technology

The high-pressure and high-tension stress layer of transparent heated glass ceramics is realized, which improves its toughness and drop resistance, while avoiding clouds and devitriification phenomena, ensuring the high optical and mechanical properties of the ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654824000009
    Figure 0007654824000009
  • Figure 0007654824000010
    Figure 0007654824000010
  • Figure 0007654824000011
    Figure 0007654824000011
Patent Text Reader

Abstract

The present invention discloses a transparent reinforced glass-ceramic having a high stress depth, the crystal phase of the reinforced glass-ceramic contains spinel crystals and zirconia crystals, but does not contain Li-containing crystals, the reinforced glass-ceramic has a compressive stress region extending from its surface to a compression depth, the depth DOL_0 of the compressive stress layer is 14% or more of the thickness of the reinforced glass-ceramic, and the tensile stress linear density of the reinforced glass-ceramic is 25000MPa / mm or more. By introducing more Li ions and Na ions into the spinel glass-ceramic component, the obtained transparent spinel glass-ceramic can be chemically reinforced, and a transparent reinforced glass-ceramic having high CS, DOL_0, CT_AV and CT_LD is obtained, and the reinforced glass-ceramic shows excellent drop resistance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of glass technology, in particular to transparent reinforced glass-ceramics with high stress depth, their manufacturing method and applications. [Background technology]

[0002] As electronic devices become thinner, the requirements for cover glass performance are gradually increasing, and microcrystalline glass (glass ceramics) have attracted wide attention due to their excellent impact resistance, scratch resistance, and abrasion resistance. Transparent spinel ceramics not only have the performance characteristics of general high-performance ceramics such as high temperature resistance, corrosion resistance, abrasion resistance, impact resistance, high hardness, and excellent insulation, but also have optical properties similar to those of white sapphire single crystals, and have good optical transmittance in the ultraviolet, visible, and infrared light bands, and are often used in transparent armor, missile windows, cowlings, various types of substrate materials, new lamps, and equipment observation windows in high-temperature, high-pressure, and corrosive environments. However, spinel microcrystalline glass generally cannot be chemically strengthened to increase toughness, so while it has high hardness, it also has poor toughness and poor drop resistance, and its brittleness is more pronounced, especially when the thickness is small (≦1mm), making it unsuitable for electronic cover glass that requires high impact resistance.

[0003] For electronic cover glass, it is required to have high CS, DOL_0, CT_AV and CT_LD, and especially high CT_LD is necessary to achieve excellent drop resistance. In order to obtain high CS, DOL_0, CT_AV and CT_LD, it is necessary to add a certain amount of Li2O and Na2O to the glass composition. However, with the increase in the amount of Li2O and Na2O added in the spinel glass ceramic composition, crystals that affect the optical performance of the glass ceramics, such as β-quartz, β-quartz solid solution, β-spodumene, etc., are often precipitated in the glass, and the precipitation of these crystals makes the glass ceramics cloudy and even devitrified, making it difficult to obtain ideal transparent spinel glass ceramics.

[0004] It is an urgent task for those skilled in the art to develop a new transparent spinel glass-ceramic having a higher amount of Li ions and Na ions for use in ion exchange for chemical strengthening while having excellent optical performance, and to use the transparent spinel glass-ceramic to produce a strengthened glass-ceramic having high CS, DOL_0, CT_AV and CT_LD and capable of achieving excellent drop resistance. Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention aims to provide a transparent reinforced glass-ceramic having a high stress depth, excellent drop resistance and excellent transmittance. [Means for solving the problem]

[0006] In order to solve the above problems, the present invention adopts the following technical solutions.

[0007] The present invention provides a transparent reinforced glass-ceramic having a high stress depth, the crystalline phase of the reinforced glass-ceramic comprising spinel crystals and zirconia crystals, and no Li-containing crystals; The reinforced glass ceramic has a compressive stress region extending from its surface to a compression depth, and the depth DOL_0 of the compressive stress region is 14% or more of the thickness of the reinforced glass ceramic. The tensile stress linear density CT_LD of the reinforced glass ceramic is 25000 MPa / mm or more.

[0008] The crystalline phase of the reinforced glass-ceramic does not include quartz or quartz solid solution.

[0009] The reinforced glass ceramic has a tensile stress linear density CT_LD of 25,000 to 40,000 MPa / mm, and preferably 27,000 to 40,000 MPa / mm.

[0010] The reinforced glass ceramic has a surface compressive stress CS of 650 MPa or more, and preferably 680 MPa or more.

[0011] The reinforced glass ceramic has an average tensile stress CT_AV of 35.0 MPa or more, and preferably 39.0 MPa or more.

[0012] The reinforced glass ceramic has a Vickers hardness of 740HV0.3 or more.

[0013] The reinforced glass ceramic has a fracture toughness of 1.500 MPa m 1 / 2 or more, preferably 1.560 MPa m 1 / 2 That's all.

[0014] The spinel crystals include zinc spinel and magnesium spinel.

[0015] At a thickness of 0.7 mm, the transmittance of the reinforced glass-ceramic at 550 nm is greater than 85.00%.

[0016] The reinforced glass-ceramics exhibit a crystallinity of at least 30.00 wt %.

[0017] The average crystal size in the reinforced glass-ceramic is 15.0 nm or less.

[0018] The reinforced glass ceramic includes a compressive stress layer located on a surface and a tensile stress layer located inside, and the composition of the tensile stress layer of the reinforced glass ceramic is, in mole percent of oxides, LiO: 3.50 to 6.00 mol%, Na2O: 2.00 to 4.00 mol% Contains each of the components.

[0019] The composition of the tensile stress layer of the reinforced glass ceramic is, in mole percent of oxide, SiO2: 50.00 to 65.00 mol%, Al2O3: 14.50 to 25.00 mol%, MgO: 3.50 to 8.00 mol%, ZnO: 8.00 to 16.00 mol%, BaO: 0 to 2.00 mol%, TiO2+ZrO2: 3.00-5.50 mol% Contains each of the components.

[0020] The composition of the tensile stress layer of the reinforced glass-ceramic, in mole percent of oxides, is: 0.40≦(Al2O3+ZnO+MgO+ZrO2+TiO2) / (Li2O+Na2O+SiO2+BaO)≦0.70.

[0021] The composition of the reinforced glass-ceramic tensile stress layer, in mole percent of oxides, is: 0.43≦(Al2O3+ZnO+MgO+ZrO2+TiO2) / (Li2O+Na 2O+SiO2+BaO)≦0.68.

[0022] The composition of the reinforced glass-ceramic tensile stress layer, in mole percent of oxides, is: Na2O / (Li2O+Na2O+SiO2+BaO)≧0.035; and / or Li2O / (Li2O+Na2O+SiO2+BaO)≧0.054.

[0023] The composition of the reinforced glass-ceramic tensile stress layer, in mole percent of oxides, is: 0.035≦Na2O / (Li2O+Na2O+SiO2+BaO)≦0.070; and / or 0.054≦Li2O / (Li2O+Na2O+SiO2+BaO)≦0.090.

[0024] The composition of the tensile stress layer of the reinforced glass ceramic is, in mole percent of oxide, SiO2: 50.00 to 63.00 mol%, preferably 50.00 to 57.00 mol%; and / or Al2O3: 14.50 to 20.00 mol%, preferably 15.00 to 19.00 mol%; and / or MgO: 3.90 to 7.60 mol %, preferably 4.00 to 7.50 mol %; and / or ZnO: 8.00 to 15.50 mol %, preferably 9.00 to 15.20 mol %; and / or BaO: 0 to 1.50 mol %, preferably 1.00 to 1.35 mol %; and / or Li2O: 3.50 to 5.00 mol%, preferably 4.00 to 5.00 mol%; and / or Na2O: 2.30 to 3.60 mol%, preferably 3.00 to 3.60 mol%; and / or TiO2: 0 to 2.00 mol%, preferably 0.30 to 1.30 mol%; and / or ZrO2: 2.50 to 5.00 mol %, preferably 2.90 to 4.20 mol %.

[0025] The present invention provides a method for producing a transparent reinforced glass-ceramic having a high stress depth, the method comprising the steps of: (1) compounding and mixing raw materials according to a recipe to produce a glass precursor; (2) subjecting the obtained glass precursor to a nucleation process and a crystallization process in sequence to produce a transparent spinel glass-ceramic; (3) subjecting the transparent spinel glass-ceramic obtained in step (2) to one or more ion-exchange steps in a salt bath to produce said transparent reinforced glass-ceramic.

[0026] In the step (2), When performing the nucleation treatment, the nucleation temperature is 700 to 800°C, and the nucleation treatment time is 30 to 1440 min; When the crystallization treatment is carried out, the crystallization temperature is 900 to 1000° C., and the crystallization treatment time is 5 to 1440 minutes.

[0027] In the step (2), when the crystallization treatment is performed, the temperature is increased at a rate of 20° C. / min or more. The temperature is raised to the crystallization temperature at a rate of preferably 25° C. / min or more, and more preferably 30° C. / min or more.

[0028] In the step (2), when the nucleation treatment is carried out, the temperature is increased to the nucleation temperature at a rate of 5 to 20° C. / min, preferably at a rate of 10° C. / min.

[0029] In the step (3), when one-stage ion exchange is performed, the salt bath composition contains 50-100 wt% NaNO3+0-50 wt% KNO3, the ion exchange temperature is 400-500°C, and the ion exchange time is 0.5-48 hours.

[0030] In the step (3), when performing the two-stage ion exchange, The salt bath composition in the first stage is 90-100wt% NaNO3 + 0-10wt% KNO3, the ion exchange temperature is 400-500℃, and the ion exchange time is 0.5-48h. The salt bath composition in the second stage contains 0-10 wt% NaNO3 + 90-100 wt% KNO3, the ion exchange temperature is 400-500°C, and the ion exchange time is 0.5-48 h.

[0031] In order to improve the life of the salt bath, a salt bath protectant may be added to the salt bath in an amount of 0.1 to 5 wt % by mass of the salt bath, and the salt bath protectant is Li + The term "antimicrobial" includes substances for inactivating, precipitating, or absorbing

[0032] The present invention further provides an electronic terminal as a consumer product, the electronic terminal comprising: a case including a front, a back and a side; an electronic component having a portion located within the case; the electronic component includes a display device located at or adjacent to a front surface of the case; the front surface and / or the back surface and / or the side surfaces comprise the reinforced glass-ceramic material; The electronic terminal further includes a cover product that covers a front surface of the case or is located on the display device, the cover product including the reinforced glass ceramic material; The consumer electronic products include mobile phones, tablets, photovoltaic devices, or other electronic devices (such as electronic watches).

[0033] The transparent spinel glass-ceramic material and the reinforced glass-ceramic material of the present invention both have excellent performance and can be included / applied in other products, such as watches, transparent armor, missile windows, cowlings, substrate materials, new lamps, observation windows for equipment in high temperature and pressure / corrosive environments, display protection materials and exterior housing protection materials for portable smart electronic devices (portable smart electronic devices include mobile phones, tablets, electronic watches, etc.), building products, transportation products (e.g. automobiles, trains, airplanes, marine aircraft, etc.), appliance products, or any products that require a certain degree of transparency, scratch resistance, impact resistance, wear resistance, or a combination thereof.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The present invention optimizes the components of spinel glass ceramic materials, and introduces more Li ions and Na ions, which are used in ion exchange for chemical strengthening, into spinel glass ceramics, thereby obtaining spinel glass ceramics that are free of impurity crystal phases (e.g., Li-containing crystal phases, quartz, quartz solid solution, and other impurity crystal phases), and the glass ceramics are free of phenomena such as cloudiness and devitrification, ensuring that the glass ceramics materials have excellent transmittance. . By introducing more Li and Na ions into the spinel glass-ceramics components, the resulting spinel glass-ceramics can be chemically strengthened to obtain transparent strengthened glass-ceramics with high CS, DOL_0, CT_AV and CT_LD, which exhibit excellent drop resistance.

[0036] 2. As a result of carrying out performance tests on the glass-ceramic material obtained in the present invention, it was found that the transparent spinel glass-ceramic material of the present invention has a high degree of crystallinity, which contributes to excellent mechanical properties of the glass-ceramic material.

[0037] 3. The present invention further provides a method for producing spinel glass ceramics. The process provided by the present invention controls the process parameters of the crystallization process and the nucleation process, and sets the required heating rate parameters, so as to finally obtain spinel glass ceramics free of impurity crystalline phases (such as Li-containing crystalline phases, quartz, quartz solid solution and other impurity crystalline phases), and ensures that the glass ceramic material has excellent optical properties. [Brief description of the drawings]

[0038] [Figure 1] FIG. 1 is a graph showing the effect of a drop test of a finished product.

[0039] [Diagram 2] FIG. 2 is a graph showing the relationship between the Li2O content and CT_LD, where D represents a comparative example and S represents an embodiment.

[0040] [Diagram 3] FIG. 3 shows DSC graphs of glass precursors with different Li contents.

[0041] [Figure 4] FIG. 4 shows the XRD graphs of the glass-ceramics obtained at different heating rates during the crystallization treatment.

[0042] [Diagram 5] Figure 5 shows photographs of glass-ceramics obtained at different heating rates during the crystallization process: (a) is glass without heat treatment, (b) is glass-ceramics obtained at a heating rate of 5°C / min during the crystallization process, (c) is glass-ceramics obtained at a heating rate of 20°C / min during the crystallization process, and (d) is glass-ceramics obtained at a heating rate of 30°C / min during the crystallization process.

[0043] [Figure 6] FIG. 6 is a graph showing the transmittance of light with a wavelength of 550 nm of glass ceramics obtained at different heating rates during crystallization treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0044] The present invention will now be described in more detail with reference to examples and drawings.

[0045] First, the special names and measurement methods related to the present invention are as follows:

[0046] Glass-ceramics: also called microcrystalline glasses, are solid composite materials containing both glassy and microcrystalline phases, obtained by targeted and controlled crystallization of base glasses.

[0047] Reinforced glass ceramics: A solid composite material obtained by chemically strengthening glass ceramics. During high-temperature chemical strengthening, alkali metal ions with large ionic radii (e.g. potassium ions, sodium ions) replace alkali metal ions with small ionic radii (e.g. sodium ions, lithium ions) in the glass ceramics in the salt bath, resulting in a difference in the volume of the exchanged ions, which creates compressive stress on the surface of the glass ceramics.

[0048] Surface compressive stress CS: After glass ceramics are chemically strengthened, the alkali metal ions with small surface radii are replaced by alkali metal ions with large radii, and the compressive stress generated on the glass surface due to the squeezing effect of the alkali metal ions with large radii is called surface compressive stress.

[0049] Depth of compressive stress layer DOL_0: The distance from the surface of the tempered glass ceramic to the position where the compressive stress is zero.

[0050] Tensile stress linear density CT_LD: the ratio of the total tensile stress obtained based on the test by the SLP stress meter to the thickness of the glass ceramic. After chemical strengthening, a tensile stress layer is formed inside the strengthened glass ceramic, and the tensile stress layer has an upper boundary at a certain distance from the upper surface of the strengthened glass ceramic and a lower boundary at a certain distance from the lower surface of the strengthened glass ceramic. In the tensile stress layer, the magnitude of the tensile stress at a point on a line segment that is perpendicular to the upper boundary and the lower boundary at the same time and whose upper and lower end points are at the upper and lower boundaries, respectively, is plotted as the Y axis and the distance from the corresponding point to the upper boundary as the X axis, which is referred to as the tensile stress curve. The ratio of the definite integral of the tensile stress curve to the thickness of the strengthened glass ceramic, i.e., the ratio of the total tensile stress of the strengthened glass ceramic measured by the SLP-2000 stress meter to the thickness of the glass, is referred to as the tensile stress linear density.

[0051] Since the compressive stress and tensile stress in chemically strengthened glass are in a balanced and equal relationship, and the test of the tensile stress area of ​​glass using the SLP-2000 stress meter is more accurate, the ratio of the tensile stress integral to the thickness is used to represent the magnitude of the stress accommodated per unit thickness of the glass ceramic, and thus represents the degree of stress in the chemically strengthened glass ceramic.

[0052] CT_AV: The average value of all tensile stresses in the tensile stress region.

[0053] Nucleation temperature: The temperature at which crystal nuclei form.

[0054] Crystallization temperature: The temperature at which the growth rate of the target crystal can be controlled.

[0055] Transmittance: When light of a certain wavelength is irradiated onto a glass surface, the light is reflected, absorbed, and transmitted, and the ratio of the intensity of the transmitted light to the intensity of the incident light is the transmittance.

[0056] Cloudy: A semi-transparent state occurring due to large crystals or phase separation in the glass-ceramic, resulting in a state between transparent and devitrified.

[0057] Devitrification: Large crystals or phase separation in the glass-ceramic cause the glass to completely lose its transparent properties, making it impossible to see through the glass to anything on the screen behind it.

[0058] Differential Scanning Calorimetry (DSC) Testing: The sample was crushed into powder and then sieved through a 200 mesh sieve. Test conditions: Room temperature to 1100°C, heating rate 10°C / min. The test equipment was a TGA / DSC3+ differential thermal / thermogravimetric simultaneous measurement device manufactured by METTLER TOLEDO.

[0059] Transmission test: The crystallized glass pieces were washed in an ultrasonic cleaner under the following conditions: Cleaning time: 5-10min. Cleaning agent used: A commonly used detergent diluted 10 times. Washing temperature: 45℃-65℃ Cleaning frequency: 20KHZ-40KHZ.

[0060] Then, the transmittance of the glass at different wavelengths is measured by a haze meter, and the results are in accordance with GB / T 7962.12-2010 Part 12 of the Measurement Method for Colorless Optical Glasses: Spectral Transmittance Testing is conducted according to the standards of the "Rate" The haze meter used in the present invention is a spectrophotometer CM-3600A manufactured by Konica Minolta.

[0061] Finished product drop test: First, 120-grit sandpaper was attached to a 160g Huawei P30 model, and a 50*50*0.7mm piece of reinforced glass ceramic to be tested was placed directly under the model, and then the model was dropped from a specified height with an impact. At least 10 samples from each lot are tested, and the samples are dropped once from a height of 0.4 m. If the sample does not break, it is raised to a height of 0.1 m each time and dropped again, continuing until the glass breaks. If the sample breaks, the average of the previous heights is the drop resistance height.

[0062] In the present invention, the stress measurement was performed using FSM6000 and SLP2000 manufactured by Orihara Co., Ltd., which can measure the high-pressure stress area in the surface layer and the low-pressure stress area in the deep layer, respectively, and the stress curve was fitted using PMC software to obtain the corresponding test results. Of course, other stress measurement devices that can measure the high-pressure stress area in the surface layer and the low-pressure stress area in the deep layer can also be used.

[0063] Second, the present invention provides a transparent spinel glass-ceramic, the glass-ceramic comprising, in terms of oxide mole percent: LiO: 3.50 to 6.00 mol%, Na2O: 2.00 to 4.00 mol% Each component of The crystalline phase of the glass-ceramics includes spinel crystals and zirconia crystals, and does not include Li-containing crystals.

[0064] The present invention focuses on the composition of glass ceramic materials, which can be chemically strengthened to increase toughness and obtain high CS, DOL_0, CT_AV and CT_LD. In order to improve impact drop resistance, it is necessary to add alkali metal oxides to the composition, especially Li2O (lithium oxide) and Na2O (sodium oxide). However, when the amount of Li2O and Na2O added increases, it always causes impurity crystals, such as β-quartz, β-quartz solid solution, β-spodumene, etc., to precipitate in the glass, which affects the optical performance of glass ceramics. Figure 3 clearly demonstrates this point, and with the increase in the content of Li2O, the single peak formed by spinel in Figure 3 gradually changes to multiple peaks (spinel peak + other impurity crystal phases). The precipitation of these impurity crystals causes the glass to become cloudy and even devitrified after crystallization, which severely affects the optical performance of glass ceramics.

[0065] To address this issue, the conventional technology usually reduces the amount of Li2O and Na2O added to avoid the precipitation of excessive β-quartz, β-quartz solid solution, β-spodumene, and other crystalline phases, thereby avoiding the clouding and devitrification of glass-ceramics. However, this method leads to a decrease in CS, DOL_0, CT_AV, and CT_LD obtained by strengthening the glass-ceramics, making it difficult to achieve an excellent level of drop resistance.

[0066] The present invention provides a transparent toughened spinel glass-ceramic with high CS, DOL_0, CT_AV and CT_LD, and optimizes the components to improve the drop resistance of the spinel glass-ceramic.

[0067] In the present invention, when Li2O and Na2O are introduced in a larger amount, a spinel glass ceramic free of impurity crystal phases (e.g., Li-containing crystal phases, quartz, quartz solid solution, and other impurity crystal phases) can be obtained, and the glass ceramic does not exhibit phenomena such as cloudiness and devitrification, ensuring that the glass ceramic material has excellent transmittance. By introducing more Li ions and Na ions into the spinel glass ceramic component, the obtained spinel glass ceramic can be chemically strengthened, resulting in a transparent strengthened glass ceramic with high CS, DOL_0, CT_AV, and CT_LD, and the transparent strengthened glass ceramic has excellent drop resistance.

[0068] The transparent spinel glass-ceramics provided by the present invention include: The LiO content may be 3.50-6.00 mol%, including all ranges and subranges therebetween, such as 3.50-5.00 mol%, 4.50-5.00 mol%, 4.50-5.50 mol%, 3.50-4.50 mol%, 4.00-5.00 mol%, 4.50-6.00 mol%, 5.00-6.00 mol%, 5.50-6.00 mol%, 3.50-4.00 mol%, 3.50-4.40 mol%, 3.80-5.50 mol%, 3.90-4.00 mol%, 3.60-4.40 mol%, 4.80-5.90 mol%, etc. In some embodiments, the LiO content can be 3.50 mol%, 3.60 mol%, 3.70 mol%, 3.80 mol%, 3.90 mol%, 4.00 mol%, 4.10 mol%, 4.20 mol%, 4.30 mol%, 4.40 mol%, 4.50 mol%, 4.60 mol%, 4.70 mol%, 4.80 mol%, 4.90 mol%, 5.00 mol%, 5.10 mol%, 5.20 mol%, 5.30 mol%, 5.40 mol%, 5.50 mol%, 5.60 mol%, 5.70 mol%, 5.80 mol%, 5.90 mol%, 6.00 mol%, etc.

[0069] The Na2O content may range from 2.00 to 4.00 mol%, including all ranges and subranges therebetween, such as 2.30 to 3.60 mol%, 3.00 to 3.60 mol%, 2.5 to 3.00 mol%, 2.40 to 3.80 mol%, 2.00 to 2.60 mol%, 2.00 to 2.80 mol%, 2.50 to 3.20 mol%, 2.50 to 3.60 mol%, 2.50 to 3.10 mol%, 2.50 to 3.40 mol%, 2.50 to 3.80 mol%, 2.80 to 3.50 mol%, 2.10 to 3.60 mol%, 2.20 to 3.80 mol%, 2.30 to 3.60 mol%, 2.30 to 3.80 mol%, 2.40 to 3.80 mol%, 2.50 to 3.60 mol%, 2.50 to 3.10 mol%, 2.50 to 3.40 mol%, 2.50 to 3.80 mol%, 2.80 to 3.50 mol%, 2.10 to 3.60 mol%, 2.20 to 3.80 mol%, 2.30 to 3.80 mol%, 2.40 to 3.80 mol%, 2.5 ... 0.90 mol%, etc., and in some embodiments the NaO content can be 2.00 mol%, 2.10 mol%, 2.20 mol%, 2.30 mol%, 2.40 mol%, 2.50 mol%, 2.60 mol%, 2.70 mol%, 2.80 mol%, 2.90 mol%, 3.00 mol%, 3.10 mol%, 3.20 mol%, 3.30 mol%, 3.40 mol%, 3.50 mol%, 3.60 mol%, 3.70 mol%, 3.80 mol%, 3.90 mol%, 4.00 mol%, etc.

[0070] In some embodiments, the crystalline phase of the glass-ceramics does not include quartz and quartz solid solutions, the presence of which can affect the optical performance of spinel glass-ceramics and can lead to the glass becoming cloudy or even devitrified after crystallization.

[0071] In some embodiments, the glass ceramics exhibit a crystallinity of at least 30.00 wt%, and the average size of the crystals in the glass ceramics is 15.0 nm or less. By controlling the crystallinity to be sufficiently high, the inherent strength of the glass ceramics can be significantly improved, and at the same time, by controlling the crystal size, the crystal size can be ensured to be sufficiently small, which can significantly improve the translucency of the glass ceramics and ensure that the glass ceramics have excellent optical performance. The glass ceramics of the present invention exhibit a crystallinity of at least 30.00 wt%, and the average size of the crystals in the glass ceramics is 15.0 nm or less. %. In some embodiments, the glass-ceramic composition of the present invention may be a glass-ceramic composition comprising at least one of the above and all ranges and subranges therebetween, for example, 30.00-50.00 wt%, 30.00-40.00 wt%, 40.00-50.00 wt%, 35.00-40.00 wt%, 30.00-44.00 wt%, 31.00-35.00 wt%, 42.00-45.00 wt%, 31.00-37.00 wt%, 30.00-38.00 wt%, 30.00-39.00 wt%, etc. The crystallinity of the coax may be 30.00wt%, 31.00wt%, 32.00wt%, 33.00wt%, 34.00wt%, 35.00wt%, 36.00wt%, 37.00wt%, 38.00wt%, 39.00wt%, 40.00wt%, 41.00wt%, 42.00wt%, 43.00wt%, 44.00wt%, 45.00wt%, 46.00wt%, 47.00wt%, 48.00wt%, 49.00wt%, 50.00wt%, etc. At the same time, the average size of the crystals in the glass-ceramics of the present invention is 15.0 nm or less, including 15.0 nm or less and all ranges and subranges therebetween, such as 5.0-10.0 nm, 5.0-11.0 nm, 5.0-13.0 nm, 4.0-10.0 nm, 3.0-15.0 nm, 6.0-13.0 nm, 7.0-12.0 nm, 2.0-10.0 nm, 5.0-14.0 nm, 4.0-9.0 nm, etc., and in some embodiments, the average size of the crystals in the glass-ceramics of the present invention may be 2.0 nm, 3.0 nm, 4.0 nm, 5.0 nm, 6.0 nm, 7.0 nm, 9.0 nm, 10.0 nm, 11.0 nm, 12.0 nm, 13.0 nm, 14.0 nm, 15.0 nm, etc.

[0072] In some embodiments, the spinel crystals include zinc spinel, magnesium spinel, and / or a solid solution of zinc spinel (ZnAl2O4) and magnesium spinel (MgAl2O4). Zinc spinel (ZnAl2O4) is a mineral with a cubic crystal system and has a spinel hardness of 7.5 to 8 on the Mohs scale and a measured density of 4.38 to 4.60. g / cm 3 At ambient pressure, the Young's modulus of zinc spinel is 290 GPa. The tensile modulus is 146 GPa and the refractive index is 1.79-1.80. Zinc spinel Zinc spinel (ZnAl2O4) and magnesium spinel (MgAl2O4) form a solid solution, and the properties of the solid solution spinel are almost the same as those of zinc spinel (ZnAl2O4). The differences between them are (zinc spinel vs. magnesium spinel): (a) low refractive index (magnesium spinel) (b) low density (Mg-spinel: 1.72 vs. zinc-spinel: 1.79-1.80); Spinel: 3.6-4.1 g / cm 3 vs. zinc spinel: 4.4-4.6 g / cm 3 ) (c) Low Young's modulus (magnesium spinel: 283 GPa vs. zinc spinel: 290 (d) high shear modulus (magnesium spinel: 155 GPa vs. zinc spinel) The high hardness, density, and high elastic constant of zinc magnesium spinel give the composite microcrystalline glass better mechanical performance than the precursor glass, which is a function of the mechanical performance of each component phase. Zinc magnesium spinel microcrystalline glass has shown excellent crack propagation resistance and scratch resistance.

[0073] In some embodiments, at a thickness of 0.7 mm, the glass-ceramics have a transmittance of greater than 85.00% at a wavelength of 550 nm. The glass-ceramics of the present invention are transparent in the visible range and exhibit a transmittance of at least about 85.00% at a wavelength of 550 nm. The glass-ceramics of the present invention have a transmittance of greater than 85.00% at a wavelength of 550 nm, including greater than 85.00% and all ranges and subranges therebetween, such as 86.00%, 87.00%, 88.00%, 89.00%, 90.00%, 91.00%, 92.00%, 93.00%, etc.

[0074] In some embodiments, in mole percent of oxide, the glass-ceramics of the present invention comprise: SiO2: 50.00 to 65.00 mol%, Al2O3: 14.50 to 25.00 mol%, MgO: 3.50 to 8.00 mol%, ZnO: 8.00 to 16.00 mol%, BaO: 0 to 2.00 mol%, TiO2+ZrO2: 3.00-5.50 mol% The composition further comprises each of the components:

[0075] Furthermore, in mole percent of oxides, the glass-ceramics of the present invention comprise: SiO2: 50.00 to 63.00 mol%, preferably 50.00 to 57.00 mol%; and / or Al2O3: 14.50 to 20.00 mol%, preferably 15.00 to 19.00 mol%; and / or MgO: 3.90 to 7.60 mol %, preferably 4.00 to 7.50 mol %; and / or ZnO: 8.00 to 15.50 mol %, preferably 9.00 to 15.20 mol %; and / or BaO: 0 to 1.50 mol %, preferably 1.00 to 1.35 mol %; and / or LiO: 3.50 to 5.00 mol %, preferably 4.00 to 5.00 mol %; and / or Na2O: 2.30 to 3.60 mol%, preferably 3.00 to 3.60 mol%; and / or TiO2: 0 to 2.00 mol%, preferably 0.30 to 1.30 mol%; and / or ZrO2: 2.50 to 5.00 mol %, preferably 2.90 to 4.20 mol % is further included.

[0076] In the present invention, SiO2 (silicon dioxide) and Al2O3 (aluminum trioxide) are the main components that constitute the glass network structure. Having sufficient SiO2 and Al2O3 can ensure that the glass has high network structure strength, which is favorable for ensuring that the glass has high inherent strength and thermal stability. If the content of SiO2 and Al2O3 is too high, it is difficult to melt the glass. Al2O3 not only provides the Al element for the precipitation of spinel crystals, but also can increase the surface pressure stress during chemical strengthening treatment.

[0077] MgO (magnesium oxide) and ZnO (zinc oxide) can provide the Mg and Zn elements necessary for the spinel crystals formed in glass ceramics. MgO can improve the high-temperature viscosity of the glass liquid, reduce the crystallization tendency and crystallization rate, and improve the chemical stability and mechanical strength of the glass. ZnO, as a network intermediate, It consumes the free oxygen in the glass to form [ZnO4] and forms a network structure of the glass. However, if too much is used, the glass becomes more susceptible to crystallization. Therefore, by adjusting the ratio of MgO and ZnO, the rate of crystal precipitation can be controlled.

[0078] BaO (barium oxide) can accelerate the melting of glass, but if the content is too high, secondary bubbles are likely to occur, making fining difficult.

[0079] TiO2 (titanium oxide) and ZrO2 (zirconia) are used as nucleating agents. ZrO2 can improve the viscosity and chemical stability of glass, but if the content is too high, it will be difficult to melt the glass. TiO2 can improve the chemical stability of glass and improve the uniformity of glass, but if the content is too high, it will cause the glass to develop color and increase the refractive index of glass. The combination of TiO2 and ZrO2 can exert an excellent nucleation effect.

[0080] The SiO2 content is from 50.00 to 65.00 mol%, including all ranges and subranges therebetween, such as 50.00 to 63.00 mol%, 50.00 to 65.00 mol%, 50.00 to 60.00 mol%, 51.00 to 63.00 mol%, 52.00 to 65.00 mol%, 53.00 to 65.00 mol%, 55.00 to 65.00 mol%, 50.00 to 57.00 mol%, 52.00 to 57.00 mol%, etc. In some embodiments, the SiO2 content can be 50.00 mol%, 51.00 mol%, 52.00 mol%, 53.00 mol%, 54.00 mol%, 55.00 mol%, 56.00 mol%, 57.00 mol%, 58.00 mol%, 59.00 mol%, 60.00 mol%, 61.00 mol%, 62.00 mol%, 63.00 mol%, 64.00 mol%, 65.00 mol%, etc.

[0081] The Al2O3 content is 14.50-25.00 mol%, including all ranges and subranges therebetween, such as 14.50-20.00 mol%, 15.00-19.00 mol%, 14.50-20.00 mol%, 15.50-20.00 mol%, 15.00-24.00 mol%, 14.90-23.00 mol%, 16.00-24.00 mol%, 17.00-25.00 mol%, 18.00-25.00 mol%, etc. In some embodiments, the Al2O3 content can be 14.50 mol%, 14.90 mol%, 15.00 mol%, 15.50 mol%, 16.00 mol%, 17.00 mol%, 18.00 mol%, 19.00 mol%, 20.00 mol%, 23.00 mol%, 24.00 mol%, 25.00 mol%, etc.

[0082] The MgO content can be 3.50-8.00 mol%, including all ranges and subranges therebetween, such as 4.00-7.50 mol%, 3.90-7.60 mol%, 3.50-4.00 mol%, 3.50-5.00 mol%, 3.50-6.00 mol%, 3.50-7.00 mol%, 4.50-6.00 mol%, 5.50-8.00 mol%, 6.50-8.00 mol%, etc. In some embodiments, the MgO content can be 3.50 mol%, 3.90 mol%, 4.00 mol%, 4.50 mol%, 5.00 mol%, 5.50 mol%, 6.00 mol%, 6.50 mol%, 7.00 mol%, 7.50 mol%, 7.60 mol%, 8.00 mol%, etc.

[0083] The ZnO content is 8.00-16.00 mol%, including all ranges and subranges therebetween, such as 8.00-15.50 mol%, 9.00-15.20 mol%, 8.00-13.00 mol%, 9.00-16.00 mol%, 10.00-16.00 mol%, 8.00-10.00 mol%, 8.00-11.00 mol%, 8.00-12.00 mol%, 9.00-14.00 mol%, 9.00-12.00 mol%, etc. In some embodiments, the ZnO content can be 8.00 mol%, 9.00 mol%, 10.00 mol%, 11.00 mol%, 12.00 mol%, 13.00 mol%, 14.00 mol%, 15.20 mol%, 15.50 mol%, 16.00 mol%, etc.

[0084] The BaO content can be 0-2.00 mol%, including all ranges and subranges therebetween, such as 0-1.50 mol%, 1.00-1.40 mol%, 0-1.00 mol%, 1.00-2.00 mol%, 1.10-2.00 mol%, 1.20-2.00 mol%, 1.10-1.50 mol%, 1.20-1.80 mol%, etc. In some embodiments, the BaO content can be 0 mol%, 1.00 mol%, 1.10 mol%, 1.20 mol%, 1.40 mol%, 1.50 mol%, 1.80 mol%, 2.00 mol%, etc.

[0085] The TiO2 + ZrO2 content is 3.00 to 5.50 mol%, including all ranges and subranges therebetween, such as 3.00 to 5.00 mol%, 3.50 to 5.00 mol%, 4.50 to 5.00 mol%, 3.10 to 4.50 mol%, 3.30 to 4.70 mol%, 3.7 0-4.50 mol%, 3.10-4.80 mol%, 4.00-5.00 mol%, 3.00-4.20 mol%, 3.20-5.10 mol%, 3.40-5.40 mol%, 3.70-5.20 mol%, 3.00-4.00 mol%, etc. In some embodiments, the TiO2+ZrO2 content can be 3.00 mol%, 3.10 mol%, 3.20 mol%, 3.30 mol%, 3.40 mol%, 3.50 mol%, 3.70 mol%, 4.00 mol%, 4.20 mol%, 4.50 mol%, 4.70 mol%, 4.80 mol%, 5.00 mol%, 5.10 mol%, 5.20 mol%, 5.40 mol%, 5.50 mol%, etc.

[0086] The TiO2 content is 0-2.00 mol%, including all ranges and subranges therebetween, such as, for example, 0.10-1.00 mol%, 0.50-1.00 mol%, 0.20-1.90 mol%, 0.40-1.20 mol%, 0.60-1.50 mol%, 0.80-1.00 mol%, 0.30-1.80 mol%, 0.20-1.50 mol%, 0.30-1.30 mol%, 0.10-1.70 mol%, etc. In some embodiments, the TiO2 content can be 0 mol%, 0.10 mol%, 0.20 mol%, 0.30 mol%, 0.40 mol%, 0.50 mol%, 0.60 mol%, 0.80 mol%, 0.90 mol%, 1.00 mol%, 1.20 mol%, 1.30 mol%, 1.50 mol%, 1.70 mol%, 1.80 mol%, 1.90 mol%, 2.00 mol%, etc.

[0087] The ZrO2 content may be 2.50-5.00 mol%, including all ranges and subranges therebetween, such as 2.60-4.50 mol%, 2.70-4.50 mol%, 2.90-4.20 mol%, 2.90-3.50 mol%, 2.80-3.70 mol%, 2.50-3.10 mol%, 2.60-4.60 mol%, 3.50-5.00 mol%, 4.50-5.00 mol%, 3.10-4.50 mol%, 3.20-4.30 mol%, 2.90-3.80 mol%, 2.70-3.80 mol%, etc. In some embodiments, the ZrO2 content can be 2.50 mol%, 2.60 mol%, 2.70 mol%, 2.80 mol%, 2.90 mol%, 3.10 mol%, 3.20 mol%, 3.50 mol%, 3.70 mol%, 3.80 mol%, 4.20 mol%, 4.30 mol%, 4.50 mol%, 4.60 mol%, 5.00 mol%, etc.

[0088] After the raw material blending is completed, it is necessary to add a clarifier to the mixture, and the clarifier is not particularly limited, but sodium chloride (NaCl), tin oxide, etc. can be used. The amount of clarifier used is 2wt% or less of the mixture weight, for example, if the weight of the mixture blended according to the recipe is 1kg, the amount of clarifier added is 20g or less. Clarifiers are auxiliary components added when blending raw materials.

[0089] In some embodiments, the glass-ceramics include, in mole percent by oxide: 0.40≦(Al2O3+ZnO+MgO+ZrO2+TiO2) / (Li2O+Na2O+SiO2+BaO)≦0.70. In the present invention, by arranging the crystallizable glasses to have such a predetermined ratio value, the glass ceramics produced from these crystallizable glasses can have the properties described in the present invention. The properties include the composition and / or amount and / or structure of the zinc spinel and magnesium spinel. For example, by specifying the components of the glass ceramic to satisfy the above molar ratio, the glass ceramics can contain zinc spinel, magnesium spinel and glass phase, thereby affecting the properties and / or characteristics of the produced glass ceramics. For example, the crystallization degree of the glass ceramics can be improved, the glass ceramics can have better intrinsic strength, higher transmittance, and can perform ion exchange quickly and effectively. When arranged as above for a crystallizable glass, such ratios allow the actual transformation process (e.g. nucleation and crystallization temperature and / or time) to take place, while forming glass-ceramics characterized by the reproducible and reliable realization of the required excellent optical properties and inherent strength. (Al2O3+ZnO+M The ratio of (Li2O+Na2O+SiO2+BaO) / (Li2O+Na2O+SiO2+BaO) ranges from 0.40 to 0.70, including all ranges and subranges therebetween, such as 0.41 to 0.51, 0.43 to 0.68, 0.42 to 0.60, 0.43 to 0.55, 0.44 to 0.58, 0.42 to 0.68, 0.45 to 0.69, 0.46 to 0.62, 0.41 to 0.54, 0.43 to 0.54, 0.44 to 0.59, 0.49 to 0.70, etc. In some embodiments, the ratio of (Al2O3+ZnO+MgO+ZrO2+TiO2) / (Li2O+Na2O+SiO2+BaO) may have a value of 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, etc.

[0090] In some embodiments, the glass-ceramics include, in mole percent by oxide: Na2O / (Li2O+Na2O+SiO2+BaO)≧0.035; and / or Li2O / (Li2O+Na2O+SiO2+BaO)≧0.054. By examining the relationship between Na2O and Li2O and other components, it was found that by restricting the amounts of Na2O and Li2O used and other components used within the above-mentioned range of the predetermined ratio value, it is possible to ensure that the glass-ceramics have excellent ion-exchange ability, and that the transparent spinel glass-ceramics obtained can have high CS, DOL_0, CT_AV and CT_LD through ion-exchange chemical strengthening.

[0091] The value of the ratio Na2O / (Li2O+Na2O+SiO2+BaO) is equal to or greater than 0.035, including all ranges and subranges therebetween, such as 0.035-0.070, 0.039-0.058, 0.035-0.051, 0.035-0.052, 0.035-0.055, 0.040-0.060, 0.055-0.060, 0.038-0.052, etc. In some embodiments, the value of the ratio Na2O / (Li2O+Na2O+SiO2+BaO) may be 0.035, 0.036, 0.037, 0.038, 0.039, 0.040, 0.043, 0.045, 0.048, 0.050, 0.051, 0.052, 0.055, 0.058, 0.060, 0.063, 0.065, 0.068, 0.070, etc.

[0092] The value of the ratio Li2O / (Li2O+Na2O+SiO2+BaO) is equal to or greater than 0.054, including all ranges and subranges therebetween, such as 0.054-0.090, 0.055-0.080, 0.056-0.074, 0.058-0.073, 0.056-0.071, 0.059-0.077, 0.055-0.065, 0.055-0.075, etc. In some embodiments, the value of the ratio Li2O / (Li2O+Na2O+SiO2+BaO) can be 0.054, 0.055, 0.056, 0.058, 0.059, 0.060, 0.063, 0.065, 0.068, 0.070, 0.071, 0.073, 0.074, 0.075, 0.077, 0.080, 0.083, 0.085, 0.088, 0.090, etc.

[0093] Third, the present invention provides a method for producing a transparent spinel glass-ceramic, the method comprising the steps of: (1) The raw materials are blended and mixed according to a recipe to produce a glass precursor. (2) The obtained glass precursor is subjected to a nucleation treatment and a crystallization treatment in that order to produce a transparent spinel glass-ceramic.

[0094] In the present invention, the raw materials are mixed according to the above recipe for 30 minutes, and after it becomes uniform, a fining agent is added as necessary, and it is melted in a platinum crucible at 1650°C for 20 hours, molded in a mold, cooled to 900°C, and then annealed in an annealing furnace at 600°C for 6 hours. The glass precursor is then subjected to a nucleation process and a crystallization process to produce a transparent spinel glass-ceramic.

[0095] To obtain the transparent spinel glass ceramic product of the present invention, the nucleation temperature is 700-800°C and the nucleation treatment time is 30-1440 min when performing the nucleation treatment, and the crystallization temperature is 900-1000°C and the crystallization treatment time is 5-1440 min when performing the crystallization treatment. Here, the nucleation treatment time refers to the time for which the crystallization furnace is heated to the set nucleation temperature according to the set heating rate and then kept at the temperature. Here, the crystallization treatment time refers to the time for which the crystallization furnace is heated to the set crystallization temperature according to the set heating rate and then kept at the temperature.

[0096] The glass precursor is placed in a crystallization furnace, and first, the temperature is raised to the nucleation temperature at a heating rate of 5-20°C / min, and the temperature is kept for 30-1440min to carry out the nucleation treatment, forming a sufficient number of crystal nuclei and ensuring the crystallinity of the glass ceramics. After the nucleation treatment is completed, the temperature is raised to the crystallization temperature at a heating rate of more than 20°C / min, and the temperature is kept for 5-1440min to carry out the crystallization treatment, precipitating the required zinc spinel and magnesium spinel, while effectively suppressing the precipitation of impurity crystal phases. After the crystallization treatment, the furnace is cooled to room temperature. By adjusting the heating rate, temperature and time of different treatment steps according to the glass ceramic composition within the above range, it is possible to ensure that impurity crystal phases that affect the transmittance of the spinel glass ceramics are not precipitated, and the glass ceramics can be prevented from becoming cloudy and devitrified.

[0097] The nucleation temperature is 700-800°C, including all ranges and subranges therebetween, such as 710-790°C, 700-720°C, 700-730°C, 700-740°C, 700-750°C, 700-760°C, 730-800°C, 740-800°C, 750-800°C, 760-800°C, etc. Nucleation treatment times are from 30 to 1440 minutes, including all ranges and subranges therebetween, such as 30 to 300 minutes, 30 to 200 minutes, 30 to 700 minutes, 30 to 500 minutes, 60 to 120 minutes, 80 to 144 minutes, 90 to 1200 minutes, 100 to 1100 minutes, 300 to 440 minutes, 100 to 500 minutes, 200 to 600 minutes, 300 to 540 minutes, 100 to 440 minutes, 300 to 440 minutes, etc.

[0098] The crystallization temperature is 900-1000°C, including all ranges and subranges therebetween, such as 900-980°C, 900-960°C, 900-950°C, 900-930°C, 920-950°C, 910-1000°C, 920-1000°C, 930-1000°C, 940-1000°C, etc. The crystallization process time is from 5 to 1440 minutes, including all ranges and subranges therebetween, such as 5 to 100 minutes, 5 to 150 minutes, 5 to 200 minutes, 50 to 300 minutes, 100 to 440 minutes, 90 to 340 minutes, 200 to 1240 minutes, 800 to 1040 minutes, 500 to 740 minutes, 900 to 1040 minutes, 200 to 340 minutes, 100 to 300 minutes, 500 to 1440 minutes, etc.

[0099] In some embodiments, the heating rate during the crystallization process affects the composition of the crystalline phase in the glass ceramics, and ultimately affects the performance of the glass ceramic product, and different heating rates can impart different structures and properties to the glass ceramic product. When the glass precursor obtained according to the recipe of the present invention is subjected to a crystallization treatment with a heating rate within the range of 0 to 20°C / min, impurity crystalline phases such as Li-containing crystalline phases (such as β-spodumene), quartz, and quartz solid solution are likely to precipitate in the glass ceramics. The inventors have found through their research that in a spinel microcrystal system, the presence of impurity crystalline phases such as β-quartz, β-quartz solid solution, and β-spodumene severely affects the optical performance of the spinel glass ceramic material, It was found that the glass ceramic material after crystallization becomes cloudy and even devitrified, and the transmittance of the obtained glass ceramic product is greatly reduced. This situation is not desirable for a cover glass product. If the heating rate is greater than 20°C / min, preferably greater than 25°C / min, more preferably 30°C / min, the Li ions introduced into the glass component always remain in the glass phase that is easy to exchange, and the impurity crystal phase that affects the optical performance of other glass ceramics does not precipitate, and does not affect the transmittance of the spinel glass ceramic. For details, refer to Figures 4 and 5.

[0100] As can be seen from Figure 4, if the heating rate during crystallization is within the range of 0 to 20°C / min, impurity crystals will precipitate in the glass (XRD graph clearly shows extra characteristic peaks), mainly β-quartz, β-quartz solid solution, β-spodumene, etc., and when viewed together with Figure 5, it can be seen that these impurity crystal phases precipitated in the glass severely affect the optical performance of the glass, causing the glass to become cloudy and even devitrified. If the heating rate during crystallization is greater than 20°C / min, 30°C / min, impurity crystals will not precipitate and the glass will remain transparent. In the present invention, when performing the crystallization treatment, the heating rate is greater than 20° C. / min to 35° C. / min, including all ranges and subranges therebetween, such as 21-30° C. / min, 22-25° C. / min, 25-30° C. / min, 23-28° C. / min, 22-30° C. / min, 23-30° C. / min, 24-30° C. / min, 25-28° C. / min, 21-35° C. / min, etc. In some embodiments, when performing the crystallization treatment, the heating rate may be 21° C. / min, 22° C. / min, 23° C. / min, 24° C. / min, 25° C. / min, 28° C. / min, 30° C. / min, 35° C. / min, etc.

[0101] The heating rate during the nucleation process affects the generation of crystal nuclei, the amount of crystal nuclei, and ultimately the crystallinity of the glass ceramics and the inherent strength of the glass ceramics. In the present invention, when performing the nucleation treatment, the heating rate is 5-20°C / min and all ranges and subranges therebetween, such as 5-10°C / min, 10-20°C / min, 11-20°C / min, 12-15°C / min, 9-20°C / min, 13-20°C / min, 10-19°C / min, 9-17°C / min, etc. In some embodiments, when performing the nucleation treatment, the heating rate may be 5°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 15°C / min, 16°C / min, 17°C / min, 19°C / min, 20°C / min, etc.

[0102] Third, the present invention provides a reinforced glass ceramic. The reinforced glass ceramic according to the present invention is manufactured by subjecting the transparent spinel glass ceramic described above to ion exchange for chemical strengthening, and the reinforced glass ceramic has a compressive stress region extending from its surface to a compression depth. The reinforced glass ceramic includes a compressive stress layer located on the surface and a tensile stress layer located inside. The compressive stress layer is a compressive stress region formed by chemical strengthening, and the tensile stress layer is a region that has not been subjected to ion exchange. The composition of the tensile stress layer of the reinforced glass ceramic is the same as that of the transparent spinel glass ceramic described above.

[0103] In practice, the transparent spinel glass-ceramics are subjected to one or more stages of ion exchange in a salt bath to produce the transparent reinforced glass-ceramics.

[0104] The transparent spinel glass-ceramics can be chemically strengthened. During the process of chemically strengthening the glass-ceramics by ion exchange, the glass-ceramics are gradually or simultaneously strengthened by K. + -Na + , Na + -Li + By carrying out the above binary ion exchange, a composite compressive stress layer is obtained after the glass ceramic is ion-exchanged, and the strengthened tempered glass ceramic has a compressive stress region extending from its surface to the compression depth.

[0105] The transparent spinel glass-ceramics can be subjected to multiple ion-exchange processes to improve the performance of the glass-ceramics. By using ion-exchange salt baths with different ion concentrations, a stress curve is generated at a selected depth, and the resulting strengthened glass-ceramics have excellent stress performance.

[0106] The crystalline phase of the reinforced glass-ceramic provided by the present invention includes spinel crystals and zirconia crystals, but does not include Li-containing crystals, does not include quartz and quartz solid solutions, and the spinel crystals include zinc spinel and magnesium spinel, and / or a solid solution of zinc spinel (ZnAl2O4) and magnesium spinel (MgAl2O4). The reinforced glass-ceramic exhibits a crystallinity of at least 30.00 wt.%, and the average size of the crystals in the reinforced glass-ceramic is 15.0 nm or less. At a thickness of 0.7 mm, the transmittance of the reinforced glass-ceramic at 550 nm is greater than 85.00%.

[0107] The depth DOL_0 of the compressive stress layer of the reinforced glass-ceramic according to the present invention is 14% or more of the thickness of the reinforced glass-ceramic. Due to the increased content of Li2O and Na2O, the glass-ceramic contains more Na ions and Li ions available for ion exchange, and a deeper compressive stress layer can be formed.

[0108] When the thickness of the glass-ceramic is 0.7 mm, the range of DOL_0 is 100.0 μm or more, including DOL_0 100.0 μm or more and all ranges and subranges therebetween, such as 100.0-125.0 μm, 100.0-127.0 μm, 100.0-135.0 μm, 100.0-140.0 μm, 100.0-112.0 μm, 100.0-115.0 μm, 100.0-116.0 μm, 100.0-112.0 μm, 104.0-120.0 μm, 106.0-111.0 μm, 108.0-120.0 μm, 104.0-120.0 μm, 108.0-120.0 μm, etc. In some embodiments, DOL_0 may be 100.0 μm, 104.0 μm, 106.0 μm, 108.0 μm, 111.0 μm, 112.0 μm, 115.0 μm, 116.0 μm, 120.0 μm, 125.0 μm, 127.0 μm, 135.0 μm, 140.0 μm, etc.

[0109] The tensile stress linear density CT_LD of the strengthened glass-ceramics according to the present invention is 25000 MPa / mm or more, including 25000 MPa / mm or more and all ranges and subranges therebetween, such as 25000-40000 MPa / mm, 27000-40000 MPa / mm, 25000-38000 MPa / mm, 25000-37000 MPa / mm, 25000-39000 MPa / mm, 27000-38000 MPa / mm, 27000-39000 MPa / mm, 28000-38000 MPa / mm, etc. In some embodiments, CT_LD can be 25000 MPa / mm, 27000 MPa / mm, 28000 MPa / mm, 37000 MPa / mm, 38000 MPa / mm, 39000 MPa / mm, 40000 MPa / mm, etc.

[0110] The surface compressive stress Cs of the strengthened glass-ceramics of the present invention is 650 MPa or more, Cs being 650 MPa or more and including all ranges and subranges therebetween, for example, preferably 680 MPa or more, preferably 700 MPa or more, preferably 750 MPa or more, preferably 800 MPa or more, preferably 900 MPa or more, preferably 1000 MPa or more, preferably 700-800 MPa, preferably 750-800 MPa, preferably 760-870 MPa, preferably 710-860 MPa, preferably 700-900 MPa, preferably 800-1000 MPa, preferably 850-1000 MPa, etc. In some embodiments, Cs is 650 MPa, 680 MPa, 700 MPa, 710 MPa, It may be 750MPa, 760MPa, 800MPa, 850MPa, 860MPa, 870MPa, 900MPa, 1000MPa, etc.

[0111] The average tensile stress CT_AV of the reinforced glass ceramic according to the present invention is 35.0 MPa or more, including CT_AV of 35.0 MPa or more and all ranges and subranges therebetween, for example, preferably 39.0 MPa or more, preferably 40.0 MPa or more, preferably 45.0 MPa or more, preferably 50.0 MPa or more, preferably 55.0 MPa or more, preferably 60.0 MPa or more, preferably 65.0 MPa or more, preferably 70.0 MPa or more, preferably 75.0 MPa or more, preferably 39.0 MPa to 65.0 MPa, preferably 35.0 MPa to 65.0 MPa, preferably 35.0 MPa to 55.0 MPa, preferably 35.0 MPa to 70.0 MPa, etc. In some embodiments, CT_AV may be 35.0 MPa, 39.0 MPa, 40.0 MPa, 45.0 MPa, 50.0 MPa, 55.0 MPa, 60.0 MPa, 65.0 MPa, 70.0 MPa, 75.0 MPa, etc.

[0112] The Vickers hardness of the reinforced glass-ceramics according to the present invention is 740HV0.3 or more, where 740 in 740HV0.3 is the Vickers hardness and 0.3 is the load value used for the measurement of 0.3 kg, including 740HV0.3 or more and all ranges and subranges therebetween, for example, preferably 760HV0.3 or more, preferably 770HV0.3 or more, preferably 780HV0.3 or more, preferably 790HV0.3 or more, preferably 800HV0.3 or more, preferably 820HV0.3 or more, preferably 830HV0.3 or more, preferably 740HV0.3 to 780HV0.3, preferably 740HV0.3 to 830HV0.3, etc. In some embodiments, the Vickers hardness may be 740HV0.3, 760HV0.3, 770HV0.3, 780HV0.3, 790HV0.3, 800HV0.3, 820HV0.3, 830HV0.3, etc.

[0113] The fracture toughness of the reinforced glass ceramics of the present invention is 1.500 MPa m 1 / 2or more, and the fracture toughness of the reinforced glass ceramic is 1.500 MPa m 1 / 2 Including all ranges and subranges therebetween, for example, preferably 1.560 MPa m 1 / 2 or more, preferably 1.500 to 1.560 MPa m 1 / 2 and preferably 1.600 to 1.700 MPa m 1 / 2 and preferably 1.500 to 1.590 MPa m 1 / 2 and preferably 1.540 to 1.600 MPa m 1 / 2 and preferably 1.500 to 1.610 MPa m 1 / 2 and preferably 1.500 to 1.630 MPa m 1 / 2 and preferably 1.500 to 1.700 MPa m 1 / 2 In some embodiments, the fracture toughness of the reinforced glass-ceramic is 1.500 MPa m 1 / 2 , 1.540MPa m 1 / 2 , 1.560MPa m 1 / 2 , 1.590MPa m 1 / 2 , 1.600MPa m 1 / 2 , 1.610MPa m 1 / 2 , 1.630MPa m 1 / 2 , 1.700MPa m 1 / 2 etc.

[0114] In the present invention, the transparent spinel glass-ceramics can be ion-exchanged to obtain a strengthened glass-ceramic product with better performance, since the glass-ceramics already have improved intrinsic strength, regardless of whether the glass-ceramics have been ion-exchanged once or multiple times.

[0115] The salt bath used in the present invention contains at least one of potassium salts and sodium salts. Nitrates are common salts used for ion exchange, but any suitable salt or combination of salts can be used.

[0116] When one-stage ion exchange is performed, the composition of the salt bath is 50-100wt%NaNO3+0- The glass ceramic contains 50 wt% KNO3, the ion exchange temperature is 400 to 500°C, and the ion exchange time is 0.5 to 48 hours. Here, the "ion exchange time" refers to the time during which the glass ceramic is placed in a salt bath at a specified temperature and mixing ratio to perform chemical strengthening.

[0117] The ion exchange temperature is 400 to 500°C, including all ranges and subranges therebetween, such as 400 to 500°C, 400 to 410°C, 400 to 420°C, 400 to 430°C, 400 to 440°C, 400 to 450°C, 400 to 460°C, 400 to 470°C, 410 to 450°C, 430 to 500°C, 440 to 500°C, etc., and the ion exchange time is 0.5 to 48h, including all ranges and subranges therebetween, such as 0.5 to 46h, 1 to 10h, 1 to 5h, 1 to 40h, 7 to 30h, 9 to 29h, 10 to 41h, 6 to 32h, 9 to 27h, 4 to 33h, 5 to 27h, 6 to 38h, etc.

[0118] The salt bath composition may be 50-100 wt% NaNO3 and all ranges and subranges therebetween, such as 50-60 wt%, 50-70 wt%, 50-80 wt%, 50-90 wt%, 60-100 wt%, 70-100 wt%, 80-100 wt%, 50-89 wt%, 64-88 wt%, 90-100 wt%, etc., and 0-50 wt% KNO3 and all ranges and subranges therebetween, such as 0-40 wt%, 0-30 wt%, 0-20 wt%, 0-10 wt%, 0-14 wt%, 0-15 wt%, 0-35 wt%, 0-45 wt%, 5-40 wt%, 20-30 wt%, etc.

[0119] When two-stage ion exchange is performed, the salt bath composition in the first stage contains 90-100 wt% NaNO3 + 0-10 wt% KNO3, the ion exchange temperature is 400-500°C, and the ion exchange time is 0.5-48 h. The salt bath composition in the second stage contains 0-10 wt% NaNO3 + 90-100 wt% KNO3, the ion exchange temperature is 400-500°C, and the ion exchange time is 0.5-48 h.

[0120] The ion exchange temperature is 400 to 500°C, including all ranges and subranges therebetween, such as 400 to 500°C, 400 to 410°C, 400 to 420°C, 400 to 430°C, 400 to 440°C, 400 to 450°C, 400 to 460°C, 400 to 470°C, 410 to 450°C, 430 to 500°C, 440 to 500°C, etc., and the ion exchange time is 0.5 to 48h, including all ranges and subranges therebetween, such as 0.5 to 46h, 1 to 10h, 1 to 5h, 1 to 40h, 7 to 30h, 9 to 29h, 10 to 41h, 6 to 32h, 9 to 27h, 4 to 33h, 5 to 27h, 6 to 38h, etc.

[0121] The first stage salt bath composition includes NaNO3 and KNO3, where NaNO3 is 90-100 wt% and all ranges and subranges therebetween, such as 91-100 wt%, 92-100 wt%, 93-100 wt%, 94-100 wt%, 95-100 wt%, 96-100 wt%, 97-100 wt%, 98-100 wt%, 99-100 wt%, etc., and KNO3 is 0-10 wt% and all ranges and subranges therebetween, such as 0-1 wt%, 0-2 wt%, 0-3 wt%, 0-4 wt%, 5-10 wt%, 2-10 wt%, 6-9 wt%, 3-8 wt%, 2-9 wt%, 1-8 wt%, etc.

[0122] The second stage salt bath composition includes NaNO3 and KNO3, where NaNO3 is 0-10 wt% and all ranges and subranges therebetween, such as 0-1 wt%, 0-2 wt%, 0-3 wt%, 0-4 wt%, 2-10 wt%, 3-5 wt%, 5-10 wt%, 6-10 wt%, 2-7 wt%, 3-7 wt%, etc., and KNO3 is 90-100 wt% and all ranges and subranges therebetween, such as 91-100 wt%, 92-100 wt%, 93-100 wt%, 94-100 wt%, 95-100 wt%, 96-100 wt%, 97-100 wt%, 98-100 wt%, etc.

[0123] In order to improve the life of the salt bath, a salt bath protectant may be added to the salt bath in an amount of 0.1 to 5 wt % by mass of the salt bath, and the salt bath protectant is Li +For example, Li + The use of phosphates, silicates, carbonates, etc. as agents to inactivate, precipitate, or absorb Li+ can avoid increasing the concentration of exchanged Li+ in the salt bath, which can affect the ion exchange performance and life of the salt bath. The salt bath protectant can be 0.1-5.0 wt% and all ranges and subranges therebetween, such as 0.1-4.0 wt%, 0.1-3.0 wt%, 0.1-2.0 wt%, 0.1-1.0 wt%, 0.2-5.0 wt%, 0.5-5.0 wt%, 4.1-5.0 wt%, 3.1-5.0 wt%, 2.6-4.5 wt%, 0.7-3.5 wt%, 0.8-2.5 wt%, 0.9-1.5 wt%, 0.8-2.5 wt%, etc.

[0124] Fourth, the present invention provides an electronic terminal as a consumer product, and the electronic terminal as a consumer product provided by the present invention includes: a case including a front, a back and a side; an electronic component having a portion located within the case; the electronic component includes a display device located at or adjacent to a front surface of the case; the front surface and / or the back surface and / or the side surfaces comprise the reinforced glass-ceramic material; The electronic terminal further includes a cover product that covers a front surface of the case or is located on the display device, the cover product including the reinforced glass ceramic material; The consumer electronic device may include a mobile phone, a tablet, a photovoltaic device, or other electronic device (eg, an electronic watch).

[0125] The transparent spinel glass-ceramic material and the reinforced glass-ceramic material of the present invention both have excellent performance and can be included / applied in other products, such as watches, transparent armor, missile windows, cowlings, substrate materials, new lamps, observation windows for equipment in high temperature and pressure / corrosive environments, display protection materials and exterior housing protection materials for portable smart electronic devices (portable smart electronic devices include mobile phones, tablets, electronic watches, etc.), building products, transportation products (e.g. automobiles, trains, airplanes, marine aircraft, etc.), appliance products, or any products that require a certain degree of transparency, scratch resistance, impact resistance, wear resistance, or a combination thereof.

[0126] 5. The present invention will be described below with reference to specific examples.

[0127] [Table 1]

[0128] [Table 2]

[0129] [Table 3]

[0130] [Table 4]

[0131] [Table 5]

[0132] [Table 6]

[0133] [Table 7]

[0134] [Table 8]

[0135] Taking Example 1 as an example, the raw materials are mixed for 30 minutes according to the recipe of Formula Scheme 1, the total amount of the mixture is 1000g, and after it becomes homogeneous, 5g of a fining agent (NaCl) is added, and it is melted in a platinum crucible at 1650°C for 20 hours, and then molded into a mold, cooled to 900°C, and then annealed in an annealing furnace at 600°C for 6 hours, and then cooled to room temperature to obtain a glass precursor. According to the corresponding process conditions in the above table, the glass precursor is sequentially subjected to a nucleation treatment and a crystallization treatment to obtain a glass ceramic product. According to the corresponding strengthening process conditions in the above table, the obtained glass ceramic product is obtained. The glass is then chemically strengthened to produce reinforced glass ceramic products.

[0136] When viewed together with Tables 1 to 6, it can be seen that in the glass recipes of Comparative Examples 13 to 16, the contents of Li2O and Na2O are lower than those of Examples 1 to 12, and therefore the CT_LD obtained after tempering treatment of the obtained glass ceramics is much lower than that of Examples 1 to 12, and some do not even reach 20,000 MPa / mm. The drop resistance of the tempered glass ceramics produced using the glass ceramics of Examples 1 to 12 is obviously superior to that of Comparative Examples 13 to 16.

[0137] The final product drop experiment was carried out by the tempered glass ceramics of Comparative Examples 13 and 15 and Examples 5, 6, 11, and 12, and 10 pieces were taken for each sample. The test results are shown in Figure 1. As can be seen from Figure 1, the drop effect of Comparative Example 13 and Comparative Example 15 is poor, and the drop height is concentrated between 0.7 and 1.7 m, while in Examples 5, 6, 11, and 12, due to the high content of Li2O in the recipe, the tensile stress line density CT_LD increases obviously after tempering, and the stress depth DOL_0 also increases obviously, and the drop height is significantly improved. At the same time, as can be seen from the CT_LD of Example 12 and Example 6 being almost at the same level, the drop height of Example 12 with high crystallinity is obviously high, and only two of the 10 pieces of glass dropped have a drop height lower than 2 m. As can be seen, in tempered glass ceramics, the drop height is related to both the crystallinity and CT_LD. The present invention not only ensures the crystallinity, but also adds a large amount of Li2O to ensure that the CT_LD after tempering is high and the drop resistance is good.

[0138] As can be seen from Tables 7 to 8, the heating rate during the crystallization process has a significant effect on the type of crystal phase of the glass ceramics. In Comparative Examples 1 to 12, the crystallization heating rate is less than 20°C / min, and the crystal phase of the glass ceramic material shows a quartz solid solution, which is an impurity crystal phase, and the size of the crystal grains is obviously large. While the crystallinity is improved, the transmittance is greatly reduced, to the point where the refractive index cannot be measured. Such glass ceramics cannot meet the requirements for use as a cover plate material.

[0139] The glass precursor obtained by the recipe of method 8 is subjected to microcrystallization treatment at different crystallization heating rates (5°C / min, 20°C / min, 30°C / min). Figure 5 shows a photograph of the glass ceramic obtained by the crystallization treatment, Figure 4 shows an XRD graph of the glass ceramic obtained by the crystallization treatment, and Figure 6 is a graph showing the transmittance of the glass ceramic to light with a wavelength of 550 nm. As can be seen from Figures 4-6, when the heating rate is within the range of 0-20°C / min during the crystallization treatment, impurity crystals are precipitated in the glass (XRD graph clearly shows extra characteristic peaks), and the glass ceramic becomes cloudy and even devitrified. When the heating rate is 30°C / min during the crystallization treatment, impurity crystals are not precipitated and the glass remains transparent.

[0140] The present invention optimizes the components of spinel glass-ceramic materials and introduces Li ions and Na ions, which are used in ion exchange for chemical strengthening, into spinel glass-ceramics, thereby obtaining spinel glass-ceramics that are free of impurity crystal phases (e.g., Li-containing crystal phases, quartz, quartz solid solution, and other impurity crystal phases), and ensures that the glass-ceramics are free of phenomena such as haze and devitrification, and that the glass-ceramic materials have excellent transmittance.

[0141] By introducing more Li and Na ions into the spinel glass-ceramics components, the resulting spinel glass-ceramics can be chemically strengthened to obtain transparent strengthened glass-ceramics with high CS, DOL_0, CT_AV and CT_LD, which exhibit excellent drop resistance.

[0142] As a result of carrying out performance tests on the glass-ceramic material obtained according to the present invention, it was found that the transparent spinel glass-ceramic material of the present invention has a high degree of crystallinity, which can contribute excellent mechanical properties to the glass-ceramic material.

[0143] The present invention further provides a method for producing spinel glass ceramics. The process method provided by the present invention controls the process parameters in the crystallization process and nucleation process, and sets the requirements for the heating rate parameters. Finally, a spinel glass ceramics without impurity crystal phases (such as Li-containing crystal phase, quartz, quartz solid solution and other impurity crystal phases) is obtained, and the glass ceramic material has excellent optical properties.

[0144] Finally, it should be noted that the above embodiments are only for illustrating the technical solutions of the present invention, and are not intended to limit the technical solutions. Those skilled in the art should understand that, without departing from the spirit and scope of the present invention, any modifications or equivalent replacements of the technical means of the present invention should be included in the claims of the present invention.

Claims

1. A transparent reinforced glass-ceramic having a high stress depth, the crystalline phase of the reinforced glass-ceramic comprising spinel crystals and zirconia crystals and being free of Li-containing crystals; The reinforced glass ceramic includes a compressive stress layer located on a surface and a tensile stress layer located inside, and the composition of the tensile stress layer of the reinforced glass ceramic is, in mole percent of oxides, Li2O: 3.50 to 6.00 mol% Na2O: 2.00 to 4.00 mol% Each component of The reinforced glass ceramic has a compressive stress region extending from its surface to a compression depth, the depth DOL_0 of the compressive stress layer is 14% or more of the thickness of the reinforced glass ceramic, and the tensile stress linear density CT_LD of the reinforced glass ceramic is 25000 MPa / mm or more. Transparent toughened glass-ceramics with high stress depth.

2. The crystalline phase of the reinforced glass ceramic does not include quartz and quartz solid solution.

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

3. The reinforced glass ceramic has a tensile stress linear density CT_LD of 25,000 to 40,000 MPa / mm.

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

4. The reinforced glass ceramic has a surface compressive stress CS of 650 MPa or more.

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

5. The reinforced glass ceramic has an average tensile stress CT_AV of 35.0 MPa or more.

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

6. The reinforced glass ceramic has a Vickers hardness of 740 HV0.3 or more.

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

7. The reinforced glass ceramic has a fracture toughness of 1.500 MPa m 1/2 The above is characterized in that 2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

8. The spinel crystals include zinc spinel and magnesium spinel.

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

9. At a thickness of 0.7 mm, the transmittance of the reinforced glass ceramic at 550 nm is greater than 85.00%.

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

10. The reinforced glass-ceramic exhibits a crystallinity of at least 30.00 wt. %.

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

11. The average size of the crystals in the reinforced glass ceramic is 15.0 nm or less.

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

12. The reinforced glass ceramic has a tensile stress linear density CT_LD of 27000 to 40000 MPa / mm, and / or The reinforced glass ceramic has a surface compressive stress CS of 680 MPa or more, and / or The reinforced glass ceramic has an average tensile stress CT_AV of 39.0 MPa or more, and / or The reinforced glass ceramic has a fracture toughness of 1.560 MPa·m 1 / 2 or more.

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

13. The composition of the tensile stress layer of the reinforced glass ceramic is, in mole percent of oxide, SiO 2 : 50.00 to 65.00 mol%, A 2 O 3 : 14.50 to 25.00 mol%, MgO: 3.50 to 8.00 mol%, ZnO: 8.00 to 16.00 mol%, BaO: 0 to 2.00 mol%, TiO 2 + ZrO 2 : 3.00 to 5.50 mol% The composition is characterized in that it contains each of the components:

2. The transparent reinforced glass-ceramic having a high stress depth according to claim 1.

14. 1. A method for producing a transparent reinforced glass-ceramic having a high stress depth, comprising: (1) compounding and mixing raw materials according to a recipe to produce a glass precursor; (2) subjecting the obtained glass precursor to a nucleation process and a crystallization process, in order, to produce a transparent spinel glass-ceramic; (3) The transparent spinel glass-ceramic obtained in step (2) is subjected to one or more ion exchange steps in a salt bath to obtain a glass-ceramic composition according to any one of claims 1 to 13. and producing the transparent reinforced glass-ceramic as described above.

15. In the step (2), When performing the nucleation treatment, the nucleation temperature is 700 to 800° C., and the nucleation treatment time is 30 to 1440 min. When performing the crystallization treatment, the crystallization temperature is 900 to 1000°C, and the crystallization treatment time is 5 to 1440 min. The method of claim 14.

16. In the step (2), when the crystallization treatment is performed, the temperature is increased to the crystallization temperature at a temperature increase rate of more than 20° C. / min. The method of claim 15.

17. In the step (2), when performing the nucleation treatment, the temperature is increased to the nucleation temperature at a rate of 5 to 20 ° C. / min. The method of claim 15.

18. In the step (3), when performing one-stage ion exchange, the composition of the salt bath is 50 to 100 wt% NaNO 3 +0~50wt%KNO 3 The ion exchange temperature is 400 to 500°C, and the ion exchange time is 0.5 to 48 h. The method of claim 14.

19. In the step (3), when performing the two-stage ion exchange, The composition of the first salt bath is 90-100 wt% NaNO 3 +0~10wt%KNO 3 The ion exchange temperature is 400 to 500° C., and the ion exchange time is 0.5 to 48 h; The composition of the second-stage salt bath is 0 to 10 wt% NaNO 3 +90~100wt%KNO 3 The ion exchange temperature is 400 to 500°C, and the ion exchange time is 0.5 to 48 h. The method of claim 14.

20. Wristwatches, transparent armor, missile windows, cowlings, circuit board materials, new lamps, equipment observation windows in high temperature, high pressure and corrosive environments, automobiles, trains, airplanes, marine aircraft, building materials, portable smart electronic devices, Application of the reinforced glass-ceramics according to any one of claims 1 to 13.

21. An electronic terminal, a case including a front, a back and a side; an electronic component having a portion located within the case; the electronic component includes a display device located at or adjacent to a front surface of the case; The front surface and / or the back surface and / or the side surface comprise a reinforced glass-ceramic material according to any one of claims 1 to 13, The electronic terminal further includes a cover product that covers a front surface of the case or is located on the display device, and the cover product includes the reinforced glass ceramic material according to any one of claims 1 to 13; The electronic terminal includes a mobile phone, a tablet, a photovoltaic device, or another electronic terminal. Electronic device.

Citation Information

Patent Citations

  • Li2O-Al2O3-SiO2-MgO-K2O-F-BASED CRYSTALLIZABLE GLASS AND CRYSTALLIZED GLASS AND MANUFACTURING METHOD OF THE CRYSTALLIZABLE GLASS AND CRYSTALLIZED GLASS

    JP2007126299A

  • Crystallized glass

    JP2021172547A

  • Ion-exchangeable transparent gahnite-spinel glass-ceramics with high hardness and elastic modulus

    JP2021505504A

  • Chemically strengthened glass

    WO2016204087A1

  • Crystallized glass substrate

    WO2020031338A1